Proposed UX model for children educational mobile application - Kaur, K. (Springer, 2019)
The evolution of mobile learning is robustly popular among children these days since the engagement is portable and owns unique interactive specialties that tends to attract more users. User experience (UX) is one of the potential approaches in designing mobile applications to deliver a complete experience for utilizing a technology. However, this concept of UX has not been adopted while designing educational mobile application for children even when researchers have claimed that childrenâs experience differs from adults. Therefore, the inadequate experience of mobile learning leads in affecting childrenâs cognitive skills in learning perspective. The problem statement argued in this paper is childrenâs cognitive skills on solving educational critical thinking problems are diminishing due to lacking of adequate elements while designing educational mobile application. To support the problem this paper aims to develop EduMobile UX Model for children when designers are developing educational mobile application for them. This study conducted a literature review to develop EduMobile UX Model. This model will be referred by designers when designing children educational mobile application. Â© Springer Nature Switzerland AG 2019.